Impact of intermittent energy restriction on anthropometric outcomes and intermediate disease markers in patients with overweight and obesity: systematic review and meta-analyses - Schwingshackl, Lukas; Zähringer, Jasmin; Nitschke, Kai; Torbahn, Gabriel; Lohner, Szimonetta; Kühn, Tilman; Fontana, Luigi; Veronese, Nicola; Schmucker, Christine; Meerpohl, Joerg J. (Critical Reviews in Food Science and Nutrition, 2020)
This systematic review aims to investigate the effects of intermittent energy restriction (IER) on anthropometric outcomes and intermediate disease markers. A systematic literature search was conducted in three electronic databases. Randomized controlled trials (RCTs) were included if the intervention lasted ≥12 weeks and IER was compared with either continuous energy restriction (CER) or a usual diet. Random-effects meta-analysis was performed for eight outcomes. Certainty of evidence was assessed using GRADE. Seventeen RCTs with 1328 participants were included. IER in comparison to a usual diet may reduce body weight (mean difference [MD]: −4.83 kg, 95%-CI: −5.46, −4.21; n = 6 RCTs), waist circumference (MD: −1.73 cm, 95%-CI: −3.69, 0.24; n = 2), fat mass (MD: −2.54 kg, 95%-CI: −3.78, −1.31; n = 6), triacylglycerols (MD: −0.20 mmol/L, 95%-CI: −0.38, −0.03; n = 5) and systolic blood pressure (MD: −6.11 mmHg, 95%-CI: −9.59, −2.64; n = 5). No effects were observed for LDL-cholesterol, fasting glucose, and glycosylated-hemoglobin. Both, IER and CER have similar effect on body weight (MD: −0.55 kg, 95%-CI: −1.01, −0.09; n = 13), and fat mass (MD: −0.66 kg, 95%-CI: −1.14, −0.19; n = 10), and all other outcomes. In conclusion, IER improves anthropometric outcomes and intermediate disease markers when compared to a usual diet. The effects of IER on weight loss are similar to weight loss achieved by CER.
CRIS-Team Scopus Importer:2020-05-22
Keywords: alternate-day fasting; continuous energy restriction; intermittent energy restriction; Meta-analysis; obesity; weight loss